VARIASI NUTRISI DAN NAUNGAN TERHADAP HASIL SELEDRI DENGAN HIDROPONIK RAKIT APUNG - Mercy Bientri Yunindanova; Linayanti Darsana; Ardianto Pradana Putra (Jurnal Agroteknologi, 2018)
Celery (Apium graveolens L) is an important horticultural commodity with a high level of demand. The fulfillment of celery needs can be done by cultivating celery with hydroponic floating system. However, cultivation of celery on a home-scale by using hydroponic floating system is often faced with the issue of shade and nutrient availability. Therefore, this study aimed to examine the effect of shade, variation of nutrients and their interaction on the growth and yield of celery. The research was conducted from March to August 2016 at Greenhouse Faculty of Agriculture, Universitas Sebelas Maret.  Research utilized two factors, namely the types of nutrients and shade levels. The nutrients composition comprised AB Mix, Composition I (NPK PhonskaTM 1g, KCl 1g, and Foliar Fertilizer GrowMoreTM 0.5 g)/L, Compostition II (NPK PhonskaTM 1 g, Foliar Fertilizer GrowMoreTM 1.5 g)/L and Composition III (Foliar Fertilizer GrowmoreTM 2.5g)/L. Shade treatments were 0%, 33%, 58% and 70%. The results showed that shading significantly decreased the growth and yield of celery. Different nutrients significantly influenced the root length but exhibited the same value on plant height, number of leaves, leaf area, number of clumps and fresh weight. There was no interaction between nutrients and shade treatments.